New insights into free and bound phenolic compounds as antioxidant cluster in tea seed oil: Distribution and contribution. (January 2021) - Wang, Xiaoqin; Contreras, María del Mar; Xu, Dunming; Jia, Wencong; Wang, Lijuan; Yang, Daomao
Abstract: Antioxidants are key agents for improving the oxidative stability of vegetable oils, but most studies have been focused on the free fraction. Alternatively, this work aimed to analyse free and bound phenolic compounds in tea seed oils from all the tea districts in China and to compare their antioxidant behaviours. The phenolic compounds were extracted using deep eutectic solvents, and 25 phenolic compounds, in both free and bound forms, were quantified by UHPLC-QqQ-MS technology. Total amounts varied from 85.5 to 119.1 μg/g, of which 61.7–77.8% were free and 22.2–38.3% were bound. The bound phenolic distribution was similar to that of the free counterparts. Subsequently, their hydrogen atom and single electron transfer activities were determined via four assays. Both free and bound phenolic compounds had significant antioxidant capacities, with high agreement between both mechanisms. Structure-activity relationship (SAR) and chemometric analyses revealed that bound phenolic compounds showed different antioxidant behaviours. Some phenolic compounds might alter the SAR and significantly contribute to the antioxidant capacities after binding. Highlights: Distribution pattern of free and bound phenols was revealed in tea seed oil. Binding was mainly affected by the amounts of phenolic compounds. Free and bound phenols had high agreement in antioxidant mechanisms. Binding might alter chemical structure and antioxidant behavior of phenolic compounds.